EFFECT OF ALIEN GENOMIC INTROGRESSIONS ON THE OSMOTIC TOLERANCE OF WHEAT - R. S. Yudina; I. N. Leonova; E. A. Salina; E. K. Khlestkina (Вавиловский журнал генетики и селекции)
Drought is one of the major environmental factors that limit crop growth and yield. Development of new wheat genotypes carrying introgressions from other cereal species is widely applied to improve the complex stability of bread wheat (Triticum aestivum L.). The aim of this study was estimation of the effect of foreign genetic material (derived from Aegilops speltoides, Ae. tauschii and T. timopheevii) on osmotic stress tolerance in wheat seedlings. Indirect evaluation of drought resistance by creating artificial shortage of moisture under laboratory conditions identified different degrees of the influence of foreign genetic material. In particular, it was shown that the presence of the T6BS· 6BL-6SL translocation from the Ae. speltoides genome in bread wheat might increase its drought resistance, whereas the presence of a T. timopheevii introgression in chromosome 2A, on the contrary, reduced the resistance of wheat to osmotic stress. By the example of translocation T5BS· 5BL-5SL, it was found that the same foreign fragment introgressed into different wheat genotypes could exert different effects on resistance to osmotic stress depending on the drought tolerance degree of the initial wheat genotype.